Positionality of Community Health Workers on Health Intervention Research Teams: A Scoping Review - Kiera Coulter; Maia Ingram; Deborah Jean McClelland; Abby Lohr (Frontiers Media S.A., 2020)
Community health workers (CHWs) are increasingly involved as members of health intervention research teams. Given that CHWs are engaged in a variety of research roles, there is a need for better understanding of the ways in which CHWs are incorporated in research and the potential benefits. This scoping review synthesizes evidence regarding the kinds of health research studies involving CHWs, CHWs' roles in implementing health intervention research, their positionality on research teams, and how their involvement benefits health intervention research. The scoping review includes peer-reviewed health intervention articles published between 2008-2018 in the U.S. A search of PubMed, Embase and CINAHL identified a total of 3,129 titles and abstracts, 266 of which met the inclusion criteria and underwent full text review. A total of 130 articles were identified for a primary analysis of the research and the level of CHWs involvement, and of these 23 articles were included in a secondary analysis in which CHWs participated in 5 or more intervention research phases. The scoping review found that CHWs are involved across the spectrum of research, including developing research questions, intervention design, participant recruitment, intervention implementation, data collection, data analysis, and results dissemination. CHW positionality as research partners varied greatly across studies, and they are not uniformly integrated within all stages of research. The majority of these studies employed a community based participatory research (CBPR) approach, and CBPR studies included CHWs as research partners in more phases of research relative to non-CBPR studies. This scoping review documents specific benefits from the inclusion of CHWs as partners in health intervention research and identifies strategies to engage CHWs as research partners and to ensure that CHW contributions to research are well-documented.